Strategi Pembelajaran Berbasis Masalah Membangun Literasi Digital Islami di Tengah Maraknya Hoaks - Annisa Anggraini; Afif Usaid; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Amid the fast and easily accessible digital information flow, hoaxes pose a serious threat to society, especially in religious contexts. This article explores the importance of implementing problem-based learning strategies to develop Islamic digital literacy, particularly among Islamic Religious Education (PAI) students and future religious educators. Through this approach, students not only learn to filter and verify information but also internalize Islamic values in their digital media use. Islamic digital literacy developed through problem-based learning helps foster a healthy and responsible digital space and strengthens the role of students as change agents in combating the spread of hoaxes